2022
DOI: 10.3390/agronomy12020456
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Carbon and Nitrogen Mineralisation of Digestates Elaborated from Distinct Feedstock Profiles

Abstract: The carbon (C) and nitrogen (N) mineralisation rates of five digestates were studied and compared with pig slurry, compost, and a solid fraction of digestate in aerobic incubation experiments. The objective was to identify the most relevant drivers of C and N mineralisation based on the physicochemical properties of the products. Net organic nitrogen mineralisation of digestates (Nmin, net) was on average 30%, although the range was relatively wide, with digestate from pig manure (39%) reaching double the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 72 publications
(100 reference statements)
3
9
0
Order By: Relevance
“…This agrees with the findings of Möller and Müller [27]. Reuland et al [26] found that anaerobic digestates had C sequestration values ranging from 20% to 81% of the total applied organic carbon (C org ) to the land, showcasing their potential to contribute to C build-up in agricultural soils. The carbon use efficiency (CUE) was negatively correlated with the content of dissolved organic carbon (DOC), which is the most available form of C org , present in the anaerobic digestates.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…This agrees with the findings of Möller and Müller [27]. Reuland et al [26] found that anaerobic digestates had C sequestration values ranging from 20% to 81% of the total applied organic carbon (C org ) to the land, showcasing their potential to contribute to C build-up in agricultural soils. The carbon use efficiency (CUE) was negatively correlated with the content of dissolved organic carbon (DOC), which is the most available form of C org , present in the anaerobic digestates.…”
Section: Introductionsupporting
confidence: 90%
“…Reuland et al [26] assessed the carbon (C) and N mineralization of several anaerobic digestates upon land application and compared them with the profiles found for other soil organic amendments (i.e., pig slurry, compost, and solid fraction of the digestate). They were able to correlate the extent of C and N mineralization with the physicochemical properties of the organic materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw and liquid digestates from cover crops exhibited a higher C mineralization and a lower N mineralization than the digestate of maize and rye silage (and 14% of chicken manure) reported by Reuland et al (2022), with slightly different incubation conditions. Raw and liquid digestates from cover crops exhibited higher C and N mineralization than other types of digestates studied by Levavasseur et al (2021), who found mean C and N mineralization of 274 mg C g −1 added C and − 18 mg N g −1 added N, respectively.…”
Section: Organic Carbon and Nitrogen Mineralizationmentioning
confidence: 62%
“…This fraction can be treated by AD due to its high biodegradability and moisture content (75-90%), although its rapid degradation could lead to acidification with high production of volatile fatty acids, limiting the anaerobic process (Ganesh et al 2022). Most of the information available for digestate composition and agricultural use refers to anaerobically digested animal manures, corn silage, sewage sludge or biowaste, all with high NH 4 + -N concentrations (Alburquerque et al 2012a;2012b;de la Fuente et al 2013;Häfner, et al 2022;Reuland et al 2022). But, little is known about the digestates produced from the AD of fruit and vegetable wastes.…”
Section: Introductionmentioning
confidence: 99%